Analisis Analisis Pertanyaan Pokok Bahasan Zat Dan Perubahannya Dalam Buku Teks IPA SMP Kelas VII Kurikulum Merdeka Berdasarkan Question Category System For Science (QCSS): Analisis Pertanyaan buku teks IPA berdasarkan Question Category System For Science (QCSS) - Ai Nurpida; Siti Romlah Noer Hodijah; Lulu Tunjung Biru (UNIB Press, 2026)
Science textbooks used as the primary learning resource should contain questions that stimulate curiosity and enhance students' thinking processes. Creative and critical thinking skills are essential skills in the 21st century. There are various types of questions, but the effectiveness of these questions in supporting learning success remains understudied. To determine the distribution of these questions, a classification using the Question Category System for Science (QCSS) can be used. This study aims to analyze the distribution and comparison of questions developed in independent curriculum science textbooks on the topic of substances and their changes based on the QCSS. The research method used is a qualitative descriptive method with a content analysis design. The data collection technique used is a document content review. The data analysis technique uses a model developed by Miles and Hubermen (1992). The results show that the questions developed in science textbook A consist of 16.36% cognitive memory questions, 52.72% convergent thinking questions, 27.28% divergent thinking questions, and 3.63% evaluative thinking questions. Furthermore, Science textbook B consists of 38.36% cognitive memory questions, 49.31% convergent thinking questions and 20.54% divergent thinking questions. Then, Science textbook C consists of 44.95% cognitive memory questions, 38.20% convergent thinking questions and 6.85% divergent thinking questions. Cognitive memory and convergent thinking questions are closed questions while divergent thinking and evaluative thinking questions are open questions. The conclusion is that the three books are dominated by closed questions and from the aspect of question distribution, Science textbook A and Science textbook B are only able to train students' critical thinking skills.